2001
DOI: 10.1007/s002210100752
|View full text |Cite
|
Sign up to set email alerts
|

Development of postural adaptation to arm raising

Abstract: We studied the development of the coordination between posture and movement by analyzing the shifts of the center of pressure (CoP) associated with arm raising. Three groups of children aged 3-5 years, 6-8 years, and 9-10 years and an adult group were tested. The subjects were required to raise their arms to the horizontal position while standing still, with their hands free or loaded (5% of the body weight). The arm movements were recorded by a TV-image processor, and the changes in position of the CoP were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…However, such functioning of postural control interpretation has been questioned (e.g., Jeka, 1995), with the postural control system clearly showing many nonlinear properties (e.g., . Young children might be more influenced by sensory manipulation because of their inability to precisely estimate their own body position based upon knowledge of body dynamics and its relationship to the environment (Barela et al, 2003), as demonstrated in several studies that investigated feedforward mechanisms in children (Assaiante, Woollacott, & Amblard, 2000;Hay & Redon, 2001;Ledebt, Bril, & Brenière, 1998;Schmitz, Martin, & Assaiante, 1999, 2002. Therefore, even without strong coupling to sensory information, any manipulation of the available information would produce a greater effect in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, such functioning of postural control interpretation has been questioned (e.g., Jeka, 1995), with the postural control system clearly showing many nonlinear properties (e.g., . Young children might be more influenced by sensory manipulation because of their inability to precisely estimate their own body position based upon knowledge of body dynamics and its relationship to the environment (Barela et al, 2003), as demonstrated in several studies that investigated feedforward mechanisms in children (Assaiante, Woollacott, & Amblard, 2000;Hay & Redon, 2001;Ledebt, Bril, & Brenière, 1998;Schmitz, Martin, & Assaiante, 1999, 2002. Therefore, even without strong coupling to sensory information, any manipulation of the available information would produce a greater effect in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Hadders-Algra (2008) reported that by these ages, postural control develops according to the multiple sensory-motor functions. Other researchers have also demonstrated that in children at these ages, vestibular function reaches the adult level (Shumway-Cook and Woollacott, 1985), the postural reference frame shifts from a body-based egocentric to a gravity-based allocentric frame (Roncesvalles et al, 2005), and the anticipatory postural control ability improves significantly (Hay and Redon, 2001). In addition, some studies have suggested that the integration of multisensory information in children aged 7-10 years enables adaptive adjustment with respect to the external environment (Forssberg and Nashner, 1982;Shumway-Cook and Woollacott, 1985;Foudriat et al, 1993).…”
Section: Evaluation Of the Developmental Process For Postural Controlmentioning
confidence: 98%
“…Two functions have been attributed to the APAs since Belenkii et al's experiments (1967): The minimization and optimization of the centre of foot pressure (CoP) displacements. Previous findings related to APAs in children reported that this population is able to produce anticipatory activities in arm raising (Hay and Redon, 2001;Riach and Hayes, 1990), tiptoe standing (Haas et al, 1989), and gait initiation (Assaı¨ante et al, 2000;Ledebt et al, 1998;Malouin and Richards, 2000). The APAs are not innate in gait initiation and must undergo development before being systematic and functional (Hayes and Riach, 1989).…”
Section: Introductionmentioning
confidence: 94%